Vol. 736 : Materials and their Application: The International Conference, Decembe 15-16, 2016, Yurga, Russia; [proceedings]; Key Engineering Materials - Valuev D. V. Denis Viktorovich; Martyushev N. V. Nikita Vladimirovich ([S. l.], Trans Tech Publications Ltd., 2017)
Title screen